In vitro-clinical correlations for amphotericin B susceptibility in AIDS-associated cryptococcal meningitis. - Larsen, R; Bauer, M; Brouwer, A; Sanchez, A; Thomas, A; Rajanuwong, A; Chierakul, W; Peacock, S; Day, N; White, N; Rinaldi, MG; Harrison, T (2007)
Reliable measures of antifungal drug susceptibility are needed. We tested the susceptibility of Cryptococcus neoformans from patients treated with amphotericin B. In vitro susceptibility employed a modified broth macrodilution method. We demonstrate a strong correlation between the quantitative measures of in vitro amphotericin B susceptibility and the quantitative response observed in patients.